A protein expression system for tandem affinity purification in Xanthomonas citri subsp citri - Dantas, Giordanni C. [UNESP]; Martins, Paula M. M. [UNESP]; Martins, Daniela A. B. [UNESP]; Gomes, Eleni [UNESP]; Ferreira, Henrique [UNESP] (Soc Brasileira Microbiologia, 2016)
Citrus canker, caused by the Gram-negative bacterium Xanthomonas citri subsp. citri (Xac), is one of the most devastating diseases to affect citrus crops. There is no treatment for citrus canker; effective control against the spread of Xac is usually achieved by the elimination of affected plants along with that of asymptomatic neighbors. An in depth understanding of the pathogen is the keystone for understanding of the disease; to this effect we are committed to the development of strategies to ease the study of Xac. Genome sequencing and annotation of Xac revealed that similar to 37% of the genome is composed of hypothetical ORFs. To start a systematic characterization of novel factors encoded by Xac, we constructed integrative-vectors for protein expression specific to this bacterium. The vectors allow for the production of TAP-tagged proteins in Xac under the regulation of the xylose promoter. In this study, we show that a TAP-expression vector, integrated into the amy locus of Xac, does not compromise its virulence. Furthermore, our results also demonstrate that the polypeptide TAP can be overproduced in Xac and purified from the soluble phase of cell extracts. Our results substantiate the use of our vectors for protein expression in Xac thus contributing a novel tool for the characterization of proteins and protein complexes generated by this bacterium in vivo. (C) 2016 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda.
Keywords: Citrus canker; Expression vectors; TAP-tag